School Sport for All: An Inclusive Developmental Framework to Improve Participation (LEARNing Landscapes, 2024)
Recognizing the contributions that school sport can make to the wellbeing of students, this paper proposes a “re-imagined” school sport framework. School Sport for All (SS4A) places students at the center of building a program where development and wellbeing are prioritized. The SS4A framework fully integrates and promotes key aspects from comprehensive school health, whole-child education, and long-term athlete development throughout all its features. As a whole, SS4A aims to ensure the benefits of sport can be experienced by all, within a school system where teaching and learning are prioritized in the classroom and in the school community.
Keywords: school sport; wellbeing; comprehensive school health; teacher-coach; whole-child education